Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Ta có
\(5^x.5^{x+1}.5^{x+2}\le10^{18}:2^{18}=>5^{3x+3}\le5^{18}=>3x+3\le18=>x\le5\)
a, \(\dfrac{7}{18}x-\dfrac{2}{3}=\dfrac{5}{18}\)
\(\dfrac{7}{18}x=\dfrac{5}{18}+\dfrac{2}{3}\)
\(\dfrac{7}{18}x=\dfrac{17}{18}\)
\(x=\dfrac{17}{18}\div\dfrac{7}{18}\)
\(x=\dfrac{17}{7}\)
a) \(\dfrac{7}{18}\).x-\(\dfrac{2}{3}\)=\(\dfrac{5}{18}\)
\(\dfrac{7}{18}\).x =\(\dfrac{5}{18}\)+\(\dfrac{2}{3}\)
\(\dfrac{7}{18}\).x = \(\dfrac{17}{18}\)
x = \(\dfrac{17}{18}\) :\(\dfrac{7}{18}\)
x =\(\dfrac{17}{7}\)
b)\(\dfrac{4}{9}\) - \(\dfrac{7}{8}\).x =\(\dfrac{-2}{3}\)
\(\dfrac{7}{8}\).x =\(\dfrac{4}{9}\)-\(\dfrac{-2}{3}\)
\(\dfrac{7}{8}\).x =\(\dfrac{10}{9}\)
x =\(\dfrac{10}{9}\) : \(\dfrac{7}{8}\)
x =\(\dfrac{80}{63}\)
c)\(\dfrac{1}{6}\)+\(\dfrac{-5}{7}\): \(\dfrac{-7}{18}\)
\(\dfrac{1}{6}\)+\(\dfrac{90}{49}\)
\(\dfrac{589}{294}\)
x-(-5)=-18
x=-18+(-5)
x=-23
x - ( - 5 ) = - 18
x + 5 = - 18
x = - 18 - 5
x = - 23
Vẫy = -23